Enhancement effects of adding internal heat exchanger on dual-pressure evaporation organic Rankine cycle. (15th February 2023) - Li, Jian; Yang, Zhen; Shen, Jun; Duan, Yuanyuan
Abstract: Dual-pressure evaporation organic Rankine cycle shows a good outlook in the power generation of medium-to-low temperature heat. Adding internal heat exchanger (IHE) is an important potential way to enhance its performance. While, the impacts of adding IHE have not been analyzed especially. The effectiveness, quantitative enhancement effects, and suitable scenarios of adding IHE need to be studied. This paper quantitatively evaluates the enhancement effects of adding IHE in the typical series dual-pressure evaporation ORC (SDORC). Impacts of heat source temperature, outlet restraint, corrosion of cold source and heat source, and organic fluid type on the enhancement effects are analyzed. The suitable scenarios for adding IHE in SDORC are revealed. Results show that adding IHE can effectively enhance the thermo-economic performance of SDORC at a sufficiently high heat source temperature, and the specific investment cost will be reduced by 3.9%. Adding IHE is also effective in enhancing the thermodynamic performance of SDORC for heat sources with outlet restraint, with a net power growth of 6.1%. For SDORC, adopting IHE fits better in the application scenarios with high heat source temperature, restrained outlet temperature, corrosive fluids, and large molecular complexity of organic fluid. The enhancement effects are more significant. Highlights: Internal heat exchanger is used in dual-pressure evaporation organic Rankine cycle. Enhancement effects of adding internal heat exchanger are quantitatively evaluated. Suitable application scenarios for adding internal heat exchanger are pointed out. Specific investment cost is reduced by 3.9% and net power is raised by 6.1%. Heat source with high temperature and outlet restraint is more suitable.